Depression and anxiety in child and adolescents with follow-up celiac disease and in their families - Esenyel, Selcen; Ünal, Fatih; Vural, Pınar (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Earlier research has indicated a positive association between Celiac disease and some mental disorders in both adults and children. The aim of this study was to explore the diet compliance and depression and anxiety levels of pediatric celiac children and their families after a gluten-free diet. Materials and Methods: A total of 30 celiac pediatric patients (17 children [57%] and 13 adolescents [43%]) were enrolled in the study, and 20 healthy controls (11 children [55%] and 9 adolescents [45%]) were studied as controls. Depression was assessed with the Children’s Depression Inventory (CDI) form, and anxiety was assessed with the Screen for Child Anxiety Related Disorders (SCARED) form. Diet compliance was measured with a diet compliance form, and the families were asked to complete the Beck Depression Measurement (BDI) form for depression and the State-Trait Anxiety Inventory I-II (STAI-I and STAI-II) forms for anxiety. Results: There was no significant difference in depression and anxiety between pediatric celiac patients consuming a gluten-free diet and the healthy control group. We observed no difference in depression and anxiety in the Celiac CD group patients. Diet compliance was 73.3% in the study group. Conclusion: The depression and anxiety levels of pediatric celiac patients and their parents did not differ from those in the healthy group.